Dampak Media Sosial terhadap Pergeseran Bahasa Gorontalo pada Generasi Muda: Analisis Konten TikTok dan Instagram - Luwiti, Sri Rumiyatiningsih (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2025)
This article examines the impact of social media on the shift in Gorontalo language usage among the younger generation, focusing on content analysis from TikTok and Instagram. Using a critical sociolinguistic approach, the study maps language patterns, identifies algorithmic and socio-cultural factors, and formulates policy recommendations. Results reveal that 85% of TikTok content tagged #Gorontalo is dominated by Indonesian, while Gorontalo appears in only 8% of content, often limited to symbolic phrases. Key drivers of the shift include the prestige of national/global languages, the scarcity of creative content in the local language, and non-proactive educational policies. However, social media also offers revitalization opportunities through initiatives such as the #AkuCintaBahasaGorontalo campaign, collaborations with digital artists, and the development of the Lonto Bahasa app. The article recommends integrating local content into platform algorithms, establishing digital language laboratories, and revising binding educational regulations. These findings underscore the necessity of multi-stakeholder collaboration to sustain Gorontalo as a living identity in the digital era.